ДОСЛІДЖЕННЯ СВІТЛОДІОДНИХ ДЖЕРЕЛ СВІТЛА У ВИПАДКУ ІМПУЛЬСНОГО ЖИВЛЕННЯ - Андрійчук, В.А.; Наконечний, М.С.; Осадца, Я.М.; Філюк, Я.О. (Інститут електродинаміки НАН України, Київ, 2020)
The researches results of the energy and dynamic characteristics for FYL-3014 and ARPL-1W LEDs with different spectral radiation when voltage rectangular pulses feds to LEDs are presented in the paper. On the basis of obtained oscilograms it is established that electrical circuits of pulsed supply of the LEDs contain hidden reactive elements of inductive and capacitive nature. The substitution schemes are proposed for these circuits and their parameters have been determined. In substitution schemes that are proposed for these circuits the LED is represented by a parallel RC link, the active component of which is determined by the heterojunction's active region resistance, and the reactive one by a capacity that is equal diffuse capacity of transition. On the basis of analysis of obtained transient processes equations for these circles it established the attenuation coefficient's dependence on the resistance of the heterojunction's active region. The influence of pulse frequency on the LEDs energy efficiency has been investigated. It is established that the maximum pulse frequency of the FYL-3014 and ARPL-1W LEDs is equal 700 kHz. References 12, figures 6.